Organizational Knowledge Network through Community of Practice - Stephan Alie (International Journal of Instructional Technology, 2022)
As the amount of critical information in companies continues to burgeon and employees’ knowledge is heralded as an organization’s key competitive advantage, knowledge management has become a compelling workplace topic of discussion. Communities of practice have recently been recognized as effective means for organizations to manage their knowledge. In order to determine how virtual communities of practice serve as knowledge management vehicles, the authors of this paper conducted a study on virtual communities of practice within twelve large, international companies by interviewing virtual community of practice builders and leaders within these organizations. This paper reveals the study’s findings. It outlines specific ways that organizations can benefit from sponsoring virtual communities of practice. It also identifies factors that community builders and leaders can influence to ensure a VCoP’s success as a knowledge management vehicle